The application value and challenges of metagenomic next-generation sequencing in the diagnosis of periprosthetic joint infection after arthroplasty - Huang, Huahui; Tong, Yan; Hu, Xiunian; Liao, Fa-ke; Chen, Rijiang (Frontiers in Medicine, 2025)
Metagenomic next-generation sequencing (mNGS) demonstrates high sensitivity, rapid diagnostic capabilities, and the potential to identify complex pathogens in periprosthetic joint infection (PJI) following arthroplasty, particularly when conventional culture methods are limited. mNGS enables the detection of polymicrobial infections and rare/fastidious pathogens, along with the ability to predict antimicrobial resistance (AMR) genes; however, the concordance between genotypic predictions and phenotypic resistance profiles requires further validation. In clinical practice, mNGS overcomes biofilm-related diagnostic barriers, facilitating early targeted antibiotic therapy and potentially reducing unnecessary revision surgeries, thereby lowering overall healthcare costs and improving patient outcomes. Nevertheless, its widespread adoption is hindered by high costs, lack of standardization, and risks of false-positive/false-negative results. Future research priorities include optimizing sample processing protocols, host DNA depletion, establishing diagnostic thresholds, and validating mNGS through integration with conventional methods. This review synthesizes recent advances in the diagnostic accuracy and clinical utility of mNGS for PJI, aiming to provide evidence-based insights for therapeutic decision-making and enhance the prevention and management of PJI.